Effect of the size of multi-layer spacer configuration on membrane performance : a CFD study - Lina Nabilah, Luqman Loke (2017)
The spiral wound membrane (SWM) module are the membrane technology for water treatment and the Reverse Osmosis (RO) membrane process is currently leading method and implemented through SWM. SWM module formed by two neighbouring membrane sheets separated by a thin net-type spacer where the separation take place. It come in multiple configurations with different spacer geometry, membrane types and size. Moreover, concentration polarization is strongly affect the performances of separation process. Spacer will reduce the extent of concentration polarization because of the enhanced wall shear thus increase the flux of the membrane. Besides, fouling also result of the concentration polarization. Fouling will increase as the concentration polarization increase then result in loss of permeate flux. Therefore, the objective of this study is to investigate the effect of the size of multilayer spacer configuration on permeate flux and concentration polarization. In the investigation, we want to reduce the concentration polarization by using difference geometry multilayer spacer configuration. Besides, ANSYS Fluent v16.2 is used to develop the 3D multilayer spacer, CFD modelling and flow of simulation.